Impact of the strategy “Peasant school for community manager leaders in food and nutrition sovereignty and security in Sumapaz, Colombia”, on some food and nutrition security and sustainable development indicators in the community - Rodríguez Rondón, María del Pilar (2022)
According to a study conducted by the National University of Colombia, the population of Sumapaz, Bogotá, Colombia, exhibited nutritional deficiencies, low food production, and lack of teamwork. The main objective of this project was to know the deficiencies, strengths, management and dynamics of the strategy Peasant School for Community Manager Leaders (ECLGC) of the Observatory of Food and Nutrition Sovereignty and Security (OBSSAN) from the National University of Colombia and the support of the Integrated Network of Southern Health Services. Another objective was to evaluate the change of knowledge and strategies of community manager leaders, as well as their role in empowerment and autonomy.Finally, prevalent food security problems were determined in order to generate solutions. Surveys reflect the precarious conditions of infrastructure and public services, as well as the scarce livelihood possibilities, despite the adequate conditions and opportunities in the area for food production and income generation. The greatest achievement was the formation of the association Red Campesina Productora de Vida y Paz de Sumapaz (Sumapaz’ Producer of Life and Peace Peasants’ Network), thus strengthening food self-consumption and increasing income due to sales.